Accidentally Emboldened: Industrial Workers between Democracy and Despotism on the Shop Floor in Wuhan, China (1984–1985) - Zhang, Yueran (International review of social history, 2025)
Existing scholarship on China's industrial politics in the early post-Mao era has not paid adequate attention to the tension between two seemingly contradictory tendencies: the reform drives to consolidate managerial despotism in urban public enterprises, and policy endeavors to strengthen formal institutional channels for workers to participate in their enterprises’ democratic management. Focusing on the city of Wuhan in 1984–1985, this article examines the policy logic behind these two overlapping tendencies and how workers experienced and reacted to them. It argues that, on the one hand, Wuhan's local authorities merely intended the institutional formalities of democracy to facilitate and build popular support for the inauguration of managerial despotism. On the other hand, workers’ very involvement in this façade of democracy accidentally emboldened many of them to air grievances, make subversive demands, assert agency, and even resist managerial despotism. These findings shed light on the nuanced historicity of 1980s China and contribute to a rethinking of the meaning of workplace democracy.